Cover Picture: Multiplexed Imaging of Protein Phosphorylation on Membranes Based on TiIV Functionalized Nanopolymers (ChemBioChem 10/2016). (17th May 2016) - Iliuk, Anton; Li, Li; Melesse, Michael; Hall, Mark C.; Tao, W. Andy
Abstract : The cover picture shows that the accurate determination of protein phosphorylation uncovers dynamic cellular signaling events that are not evident from protein expression levels. The most dominant biochemical assay, western blotting, is limited by inadequate availability and the poor quality of phospho‐specific antibodies for phosphorylated proteins. Multiplexed assays based on antibodies are further constrained by steric interference between the antibodies. Soluble nanopolymer, pIMAGO, functionalized with Ti IV ions for chelating phosphoproteins in high specificity and with infrared fluorescent tags, is capable of universally detecting phosphoproteins. In combination with regular antibodies, this allows for multiplexed imaging and accurate determination of protein phosphorylation on membrane. We anticipate broad applications of this new strategy in monitoring cellular signaling pathways and discovering new signaling events. More information can be found in the communication by W. A. Tao et al. onpage 900 in Issue 10, 2016 (DOI:10.1002/cbic.201600068 ).